Potato (Solanum tuberosum L.) Planlet Acclimatization on Various Auxin Concentrations and Growing Media - Frezananda, Audrey; Wijayani, Ari (J-PEN Borneo : Jurnal Ilmu Pertanian, 2024)
The provision of quality potato seeds is a problem faced by farmers. Tissue culture propagation is an effort to increase the availability of quality seeds. The success of tissue culture is influenced by the ability to control environmental conditions, growth regulators, and growing media at the acclimatization stage. The research aims to determine the interaction between the use of auxin concentrations and the planting medium and to obtain the appropriate concentration of auxin and planting medium for potato acclimatization. The research used a split-plot design with 2 factors and 3 replications. The main plot is the auxin concentration consisting of 3 levels; 1 ppm, 2 ppm, and 3 ppm. Subplots are planting media consisting of 3 levels; husk charcoal:vermicompost, cocopeat:vermicompost, and husk charcoal:cocopeat:vermicompost. Data were analyzed using ANOVA and followed by DMRT at a 5% level. The results showed that there was an interaction between the treatment of 3 ppm IAA concentration and the planting medium of husk charcoal:cocopeat:vermicompost on the plant height parameter 4 WAP. The IAA concentration of 3 ppm was better than the concentration of 1 ppm in the parameter number of leaves 8 WAP. The growing media of husk charcoal:cocopeat:vermicompost was better than the growing medium of charcoal husk:vermicompost on the parameters of plant height 8 WAP, number of leaves 8 WAP, leaf length and leaf width 8 WAP.